Bibliometrik: Technology-Organisation- Enviroment, Intention To Adopt Technology Pada UKM Menggunakan Analisis Vosviewer - Hafizni, Rihan (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Abstract.The development of digitalization is accelerating, along with the growth of internet usage. This condition makes a very drastic change for the company, where there is a change in the system from conventional to digital systems. SMEs need to adopt digital technology to expand the market because using a digital system all products and services produced can be seen and accessed by everyone without limits. SMEs must be able to compete to improve performance. This research is a bibliometric study that aims to identify the factors involved in the TOE model that influence SMEs to adopt the technology. Bibliometric analysis was performed using Vosviewer software. The results obtained based on the Vosviewer network mapping, are keywords that have the potential to be investigated more deeply related to the factors that influence SMEs in adopting technology.